Angiotensinogen M235T gene variants and its association with essential hypertension and plasma renin activity in Malaysian subjects: a case control study - Say, Yee How; Ling, King Hwa; Duraisamy, Ganasothie; Isaac, Suzanne; Rosli, Rozita (BioMed Central, 2005)
Background: Essential hypertension is a major public health concern worldwide where its prevalence accounts for various cerebrovascular diseases. A common molecular variant of angiotensinogen (AGT), the precursor of potent vasoactive hormone angiotensin II, has been incriminated as a marker for genetic predisposition to essential hypertension in some ethnics. This case-control study was designed not only to determine the association of the AGT M235T gene variants with essential hypertension, but also its relationship to Plasma Renin Activity (PRA) in subjects attending the Health Clinic, Kuala Lumpur, Malaysia. Methods: The study involved 188 subjects, 101 hypertensives and 87 normotensives. Consents were obtained from all the participated subjects. M235T gene variants were investigated using allele specific polymerase chain reaction and PRA was determined by radioimmunoassay. Hypertensinogenic factors such as dietary habits, physical activity, smoking and drinking habits were assessed using a pre-tested questionnaire. Results: The genotype and allele distribution of the M235T variant differed significantly in hypertensives and normotensives (χ2 = 23.184, P < 0.001 and χ2 = 21.482, P < 0.001, respectively). The odds ratio for hypertension was 1.36 (95% confidence interval 1.03–1.80) for subjects with homozygous mutated allele TT of the M235T variant compared with other genotypes or 1.98 (95% confidence interval 1.46–2.67) for those carrying T allele compared to those carrying M allele. Plasma Renin Activity is also significantly higher in hypertensive subjects (PRA = 3.8 ± 2.5 ngAI/ml/hr for hypertensives, PRA = 2.6 ± 1.3 ngAI/ml/hr for normotensives, P < 0.001), but was not significantly different between groups of genotypes (P = 0.118). Conclusion: The M235T variant of the AGT is significantly associated with essential hypertension whereas the genotype TT or allele T is a possible genetic marker or risk factor for hypertension in Malaysian subjects.